Boundedness for Commutators of Rough p-Adic Hardy Operator on p-Adic Central Morrey Spaces - Naqash Sarfraz; Muhammad Aslam; Fahd Jarad (Journal of Function Spaces)
In the present article we obtain the boundedness for commutators of rough p-adic Hardy operator on p-adic central Morrey spaces. Furthermore, we also acquire the boundedness of rough p-adic Hardy operator on Lebesgue spaces.